2009
DOI: 10.1111/j.1469-0691.2009.02842.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal and endocervical microorganisms in symptomatic and asymptomatic non-pregnant females: risk factors and rates of occurrence

Abstract: Physiological or non-physiological factors may affect the vaginal flora. The occurrence of genital microorganisms in non-pregnant females of all ages was studied, as were the risk factors associated with each microorganism. A retrospective analysis of vaginal and endocervical cultures and wet smears from 27,172 non-pregnant women, between 1996 to 2005, was performed taking into consideration clinical and socio-demographic characteristics. No microorganisms were observed in 55.7% of the individuals studied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
4
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 36 publications
12
59
4
15
Order By: Relevance
“…Table 2 LGTI with respect to CD4 cell counts in HIV-seropositive women The present study also reported increase in prevalence of candidiasis in HIV-seropositive women, which was 43.2 % as compared to 18 % in the HIV-uninfected women of reproductive age group, and like other LGTI, risk of candidial vaginal colonization increases with lower CD4 cell counts [3,7]. Likewise in the study conducted by McClelland et al, the risk of vaginal candidiasis in HIV-positive women with decreasing CD4 cell counts showed stepwise increase as compared with the risk in seronegative women [7].…”
Section: Trichomoniasis and Hivsupporting
confidence: 50%
See 1 more Smart Citation
“…Table 2 LGTI with respect to CD4 cell counts in HIV-seropositive women The present study also reported increase in prevalence of candidiasis in HIV-seropositive women, which was 43.2 % as compared to 18 % in the HIV-uninfected women of reproductive age group, and like other LGTI, risk of candidial vaginal colonization increases with lower CD4 cell counts [3,7]. Likewise in the study conducted by McClelland et al, the risk of vaginal candidiasis in HIV-positive women with decreasing CD4 cell counts showed stepwise increase as compared with the risk in seronegative women [7].…”
Section: Trichomoniasis and Hivsupporting
confidence: 50%
“…The prevalence of bacterial vaginosis, trichomoniasis, and candidiasis is estimated 8-23, 3.2, and 18 % respectively [1][2][3]. There is a complex interaction between HIV infection and LGTI.…”
Section: Discussionmentioning
confidence: 99%
“…Otros de los microorganismos que se encuentran frecuentemente en el tracto genitourinario de pacientes sintomáticos y asintomáticos son los Mollicutes (Tibaldi et al, 2009 Ureaplasma urealyticum posee la singular capacidad de hidrolizar la urea. Es potencialmente patógeno y tiene un rol etiológico infecciones del tracto urinario y genital (Gdoura et al, 2007).…”
Section: Bacteriasunclassified
“…Ureaplasma urealyticum ve Mycoplasma hominis insan genitoüriner sisteminde (GÜS) asemptomatik olarak bulunmasının yanı sıra infertilite, orşit, prostatit ve nongonokoksik üretrit gibi klinik tablolar ile ilişkilen-dirilmektedir (15,25,31) . Bu mikroorganizmaların gebelerde koryoamniyonit, erken doğum ve düşük gibi patolojilerle ilişkili oldukları ve doğum sonrasında yenidoğanda akciğer patolojileri, bakteriyemi ve menenjit gibi komplikasyonlara neden olabilecekleri ileri sürülmüştür (4) .…”
Section: Introductionunclassified